Intravitreal dexamethasone implant (Ozurdex®) findings over time: ultrasound and ultra-widefield fundus photography - Gabriela Assumpção Brito Pereira Pellegrini; Arnaldo Furman Bordon; Norma Allemann (International Journal of Retina and Vitreous)
Abstract Background Ozurdex® (Allergan®, AbbVie Company, North Chicago, Illinois, EUA), is composed of 0.7 mg of dexamethasone, fused in a solid biodegradable PLGA polymer, whose degradation occurs naturally in the vitreous cavity, usually in six months after its application. Methods In this study, we included patients aged ≥ 18 years with one or two eyes who had an indication for Ozurdex® implants. Eyes submitted to Ozurdex® application were evaluated in the first hour after the injection via transpalpebral contact B-scan ocular ultrasonography (Aviso® or Compact Touch®, Quantel®) and non-mydriatic ultra-widefield fundus photography (California®, Optos®) performed sequentially. The exams were executed using similar parameters and techniques, by the same ophthalmologist, after every 45 days, until the end of 180 days. The programed visits were the initial (tagged D0) and sequential (D45, D90, D135, and D180) visits, with a possible variance of seven days, before or after. The ultrasonographic Ozurdex® findings evaluated were: non-quantitative: structure, height, reflectivity, artifact production, location, and movement; and quantitative: length and thickness. Ultra-widefield fundus photography parameters were: Ozurdex® visualization, location, and structure. Results The B-scan showed the implant initially, at the D0 visit, as a well-delimited and homogeneously highly reflective linear and continuous structure. On D45, Ozurdex® implants presented with low internal reflectivity and irregularity in the limits. On D90, D135, and D180, reductions in the length and thickness progressively lessened, leading to the final appearance of a small highly reflective clust. Over time, all the implants presented reductions in length and thickness. The mean length at D0 was 7.42 ± 0.39 mm and at the final visit (D180) it was 1.50 ± 0.47 mm. The mean thickness at D0 was 0.77 ± 0.13 mm and at the final visit (D180) it was 0.44 ± 0.18 mm. Conclusions Considering implant dimensions, the change in length over time was more evident than the change in thickness. In all the cases where visualization was possible, positive correlations with B-scan findings were found despite changes in patient position. These alterations evidenced in the Ozurdex® implant over time may be related to the degradation of the glucose polymer structure.